Optimising management of self-inflicted burns: a retrospective review. (2nd June 2019) - Houschyar, Khosrow S.; Tapking, Christian; Duscher, Dominik; Maan, Zeshaan N.; Sheckter, Clifford C.; Rein, Susanne; Chelliah, Malcolm P.; Nietzschmann, Ina; Weissenberg, Kristian; Reumuth, Georg; Schulz, Torsten; Branski, Ludwik K.; et al.
Abstract : Objective: Self-inflicted burns typically result in extensive injuries requiring intensive care and attention in a specialised burn unit. Burn units should be familiar with the optimal management of self-inflicted burns, including the psychological and psychiatric treatment. This paper describes the experiences of managing these challenging injuries in a German burn centre. Methods: A retrospective review of patients with self-inflicted burns admitted to the burn centre between 2000 and 2017. Demographics, details of injury, presence of psychiatric disorder, clinical course, operative management and patient outcomes were recorded and compared with a control group without self-inflicted burns. Outcome measures included graft take rate, complications and need for further surgery. Results: There were a total of 2055 burn patient admissions, with 17 cases (0.8%) of self-inflicted burns. The mean age was 36±11 years with an mean percentage total body surface area (%TBSA) burned of 43.5±22.5% which was not significantly different from the control group (p=0.184). Schizophrenia and personality disorder were the most common diagnoses in the self-inflicted burns patients (n=11; 65%). Of these, four had sustained previous self-inflicted burns. Length of hospital stay was significantly longer in the self-inflicted burn group than in the control group (49.0±16.7 days, respectively, p=0.002). Conclusion: Attempted suicide by self-inflicted burns represents <1% of burn admissions. This population demonstrates a high incidence of prior psychiatric disorders. Successful treatment includes multidisciplinary management of acute medical, surgical, and psychiatric care.